The The Influence of Islamic Corporate Governance, Sharia Compliance, and Internal Control on Fraud in Islamic Commercial Banks for the Period 2019-2023 - Isna Imroatul Khusna; Maulida Nurhidayati (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: The main issue is the fluctuation in the number of frauds in Islamic Commercial Banks from 2019-2023. Bank implements compliance with Sharia Compliance through measuring variables and governance with a composite value of 1-3. However, the existence of these components does not necessarily reduce fraud cases in each Islamic Commercial Bank. Research Methods: The ordinal logistic regression model was chosen as the analysis technique using SPSS 23 software as an analysis tool. Results: Sharia Supervisory Board variable has a positive but insignificant effect on fraud. While the Board of Commissioners variable has a positive effect and the Profit Sharing Ratio has a significant negative effect on fraud. Then, the Board of Directors variable has a negative but insignificant effect on fraud. Furthermore, the Directors' Employees Welfare Ratio and Internal Control variables have a positive but insignificant effect on fraud. Conclusion: The hope is that Islamic Commercial Banks will reduce the potential for fraud by strengthening Islamic Corporate Governance and Sharia Compliance.